Revision of three species of Euonymus (Celastraceae) from China - Du, Cheng; Zuo, Yunjuan; Ma, Jinshuang (Phytotaxa, 2013)
Through field observations, recollections at known sites and researches on specimens and literature, full descriptions of Euonymus wui, Euonymus pseudovagans and Euonymus mengtzeanus are provided for the first time. The systematic position of Euonymus wui is confirmed to be within sect. Euonymus subsect. Euonymus ser. Pseudovyenomi subser. Pentameri and Euonymus mengtzeanus is confirmed to be within sect. Euonymus subsect. Euonymus ser. Pseudovyenomi subser. Pentameri. Lectotypes for Euonymus pseudovagans and Euonymus mengtzeanus are here designated. Additionally, the conservation status of the three species is evaluated according to IUCN standards (version 3.1).